Chinese (Taiwan) Yearbook of International Law and Affairs, Volume 29 (2011). - Ma, Ying-jeou. (Boston : BRILL, 2020)
The Chinese (Taiwan) Yearbook of International Law and Affairs includes articles and international law materials relating to Asia-Pacific and the Republic of China on Taiwan.
Department of Health's Declaration of Participation in the World Health Assembly (WHA).
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books